Economic reasoning on the correlation between life expectancy and economic development: Exploring alternative routes - Nadine Wittmann (Kiel Institute for the World Economy (IfW), 2014)
Regarding the connection between economic development and public health, the statistically evident correlation between a country's gross domestic product and life expectancy is widely discussed. An important aspect that keeps resurfacing in discussions on why the relationship between the latter appears to trail off or even reverse its sign once a certain gross domestic product level has been reached is that of increasing economic and social inequality of distribution within many industrialized nations. However, from an economics perspective, it seems as though further plausible explanations can be identified, whose origins are in part inherent to the special structural characteristics of the market for health but are also well known in the fields of political as well as natural resource economics. While many seminal publications focus on the demand for health, this paper takes a holistic approach toward modeling the health market, in order to account for the fact that health products are not only an input factor to people's health but also that people's health is an essential and heterogeneous input factor to health products suppliers' profit functions. Results show that this approach can substantially affect health market outcomes.
Keywords: D40; I14; I15; I18; 330; market for health; market structure; public health; life expectancy; economic development